2009
DOI: 10.1007/s11998-009-9206-0
|View full text |Cite
|
Sign up to set email alerts
|

The application of x-ray powder diffraction for the analysis of synthetic organic pigments. Part 1: dry pigments

Abstract: This paper presents x-ray powder diffraction data for over 200 synthetic organic pigments. These pigments, most manufactured in the last 130 years, are frequently found in modern works of art. Their identification is of interest in the field of art conservation for the purposes of dating works of art as well as making conservators and curators aware of issues with lightfastness and solubility. Most classes of these pigments, including b-naphthol, Naphthol AS, mono-and di-arylide yellows, quinacridones, copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…The averaged d values and diffractogram patterns are very close and cannot be considered as reliable markers to discriminate PB15:0 from PB15:1 and PB15:3 from PB15:4. The similarity of the d spacings is confirmed by the XRD results reported by Lomax . Nevertheless, it is important to note that compared with the unstabilised α‐ and β‐CuPc, the intensities recorded decrease significantly for samples corresponding to the stabilised α‐ and β‐CuPc samples.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The averaged d values and diffractogram patterns are very close and cannot be considered as reliable markers to discriminate PB15:0 from PB15:1 and PB15:3 from PB15:4. The similarity of the d spacings is confirmed by the XRD results reported by Lomax . Nevertheless, it is important to note that compared with the unstabilised α‐ and β‐CuPc, the intensities recorded decrease significantly for samples corresponding to the stabilised α‐ and β‐CuPc samples.…”
Section: Resultssupporting
confidence: 77%
“…About the polymorphism of the actual CuPc blue pigments, Raman data have been reported by Lutzenberger and Scherrer et al . The X‐ray powder diffraction (XRD) data obtained for dry pigments of CuPc have been reported by Lomax . Lomax et al .…”
Section: Introductionmentioning
confidence: 94%
“…This difference could be explained by the paint formulation and/or the CuPc crystals orientation in the paint film. In accordance with the results of the study carried out by Lomax (2010), in the present study the XRD method has appeared significantly less efficient for oil-based paints than for acrylic paints.…”
Section: Oil-based Paintssupporting
confidence: 89%
“…The relative intensities of these peaks are respectively 27 and 52 %. The diffraction peak at d D 3:34 could also be attributed to BaSO 4 but its relative intensity is much more in accordance with the strongest peak reported for PG7 (Lomax 2010). Although phthalo blue in theˇ-form is the greenest in shade (Herbst et al 2004), the SF60 greenish blue shade mainly results from the presence of PG7 in the mixture.…”
Section: Paints From Sam Francis' Studiosupporting
confidence: 68%
“…Although synthetic organic pigments themselves are crystalline, X‐ray powder diffraction (XRD) is of moderate success when trying to analyze paints. The presence of the fillers and extenders in these paints can be challenging, although Brostoff et al . found that peaks related to many synthetic organic pigments correspond to large d‐spacings (relatively large unit cells for organic vs inorganic pigments), minimizing interferences from common inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%